Cervicothoracic Intradural Spinal Lipoma Without Dyraphism Diagnosed Postpartum. Issue 1 (1st January 2015) - Teneyuque, Nicholas; Porter, Kathy B.; Pennington, Thomas
ABSTRACT: Background: Intradural spinal lipoma without evidence of dysraphism is a rare occurrence comprising approximately 1% of all spinal tumors. Case: An 18-year-old female who, following her primary cesarean section, began developing progressively worsening lower extremity weakness, paresthesias, spasticity, and hyperreflexia. Magnetic resonance imaging diagnosed a cervicothoracic intradural spinal lipoma. She underwent an osteoplastic laminotomy with subtotal resection of intradural lipoma with an excellent prognosis. Conclusion: This case highlights the need for broad differential diagnoses if symptoms do not correlate with the typical postpartum recovery. Our patient's case is the first to describe symptoms developing postpartum with excellent prognosis because of rapid evaluation and diagnosis.